A RESEARCH ON THE PROFILE OF CULTURAL CONSUMPTION OF THE STUDENTS OF THE FEDERAL UNIVERSITY OF CEARÁ, BRAZIL - Thiago Andrade Sales; Pablo Urano de Carvalho Castelar; Alesandra de Araújo Benevides (Economia & Região, 2019)
This work seeks to analyze the behavior of the consumption of cultural goods by the students of the Federal University of Ceará - UFC. A questionnaire was used as a way of capturing and manipulating the data so that economic and social aspects of the agents could be observed, as well as more questions related to their cultural consumption, frequency of use and degree of importance. From this, a probit model was elaborated in which the behavior of the consumption of cultural goods is analyzed through some exogenous variables such as: the use of cultural goods within the university; Years of study in undergraduate courses at the university; Age of students; Income and sex. It was verified that the use of cultural goods made available by the university tends to increase the consumption of cultural goods in general, as well as in relation to the years of study of the students in undergraduate courses. However, cultural consumption seems to decrease as age increases, and there seems to be a disconnect between the availability of cultural goods and the perception of the students about the supply of such goods